The Influence of Foreign Trade, Consumption, and Inflation on Economic Growth in 5 ASEAN Countries - Ananda Fitriani, Widya; Astina, Chahayu; Safarida, Nanda (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study analyzes the impact of foreign trade, consumption, and inflation on economic growth in five ASEAN countries (Indonesia, Malaysia, Singapore, the Philippines, and Thailand) during the period of 2017-2021. The research utilizes secondary data in the form of panel data. The panel data regression method is applied to assess the relationship between independent and dependent variables. The result indicate that exports significantly positively affect economic growth, while imports and consumtion do not have a significant impact. Inflation also shows a significant positive effect. These finding highlight the importance of foreign trade and inflation in influencing economic growth in the ASEAN region.